Франкові “Конкістадори”: поетизація здобувницького героїзму - Нахлік, Є. (Слово і Час, 2018)
Уперше розглянуто вірш І. Франка “Конкістадори” (1904) в контексті його творів (“Захар Беркут”, “Великі роковини”, “Мойсей” та ін.) і праць (“Темне царство”, “На склоні віку”, “Подуви весни в Росії”, “Що таке поступ?”, “Поема про сотворення світу”), поем Т. Шевченка “Гамалія” та “Кавказ” і роману Миколи Хвильового “Вальдшнепи”. Доведено, що іспанські та португальські конкістадори для Франка – лише привід і засіб для поетичної алегоризації: абстрагуючись від історичної трагедії американських тубільців, автор на прикладі відчайдушної одваги й завзяття конкістадорів виховує в українців готовість до беззастережної, при потребі збройної боротьби за національну свободу й державність. For the first time, I. Franko’s poem “Conquistadors” (1904) is considered in the context of his literary writings (“Zakhar Berkut”, “Great Anniversary”, etc.), and works supporting the liberation struggle of the enslaved peoples and blaming the occupation of foreign lands (“The Dark Kingdom”, “On the Slope of the Age”, “Spring Breath from Russia”, “What is Progress?”, “Poem about the Creation of the World”). In particular, attention is paid to Franko’s statements about A. Pushkin and M. Lermontov in connection with the Russian-imperial conquest of the Caucasus. The poems of Taras Shevchenko “Hamalia” and “Caucasus” as well as the novel “Woodcocks” (“Valdshnepy”) by Mykola Khvylovyi are also taken into consideration. The researcher assumes that the title of Franko’s poem “Great Anniversary” was a reminiscence of the eponymous poem by Ksenofont Klymkovych. As to I. Franko’s notion of heroism, it is argued, that the poem “Conquistadors” is not about the past conquest of America, but rather about the future achievement of Ukraine’s freedom, not about the heroism of old conquistadors, but rather about future liberation, or, as Bohdan Kravtsiv called it, “bellicose” (“zdobuvnytskyi”), heroism of Ukrainians. Spanish and Portuguese conquistadors served only as a ground and means for Franko’s poetic allegory. Leaving the historical tragedy of American natives beyond attention, the author, on the example of reckless courage and enthusiasm of conquistadors, prepares Ukrainians for an unconditional, if necessary armed, struggle for national freedom and statehood. The “Conquistadors” are in the line with Franko’s contemplations of that time concerning the issue of force in history. The poem “Moses” (1905), in which the Jewish ideals of the ‘state’, ‘the magnificent promised land’ were allegorically projected on the struggle for Ukrainian statehood, became the extension of Franko’s thoughts. The last stanzas of the poem are the poetization of the armed force used for getting the “promised land”. Впервые рассматривается стихотворение И. Франко “Конкистадоры” (1904) в контексте его произведений (“Захар Беркут”, “Великая годовщина”, “Моисей” и др.) и трудов, в частности, высказываний об А. Пушкине и М. Лермонтове в связи с покорением Кавказа. Обосновывается, что испанские и португальские конкистадоры для И. Франка – т олько повод и средство для поэтической аллегоризации: абстрагируясь от исторической трагедии американских туземцев, автор на примере отчаянной отваги и рвения конкистадоров воспитывает в украинцев готовность к безоговорочной, при необходимости вооружённой, борьбе за национальную свободу и государственность.